Triflumuron induces cytotoxic effects on hepatic and renal human cell lines. Issue 8 (30th March 2020) - Timoumi, Rim; Amara, Ines; Ben Salem, Intidhar; Abid‐Essefi, Salwa
Abstract: Insect growth regulator insecticides are a new class of pesticides, commonly used around the world to control insect damages. Among those compounds, we focused our interest on triflumuron (TFM), which is less toxic than other conventional insecticides. However, not much is known about its toxic effects on mammalian systems. Therefore, our study aimed toward evaluating the cytotoxic and genotoxic effects of TFM using two different cell lines, the human renal embryonic cells (HEK 293) and hepatocytes (Hep G2). We showed, according to the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, that TFM reduced significantly the cell viability and increased the reactive oxygen species generation, malondialdehyde levels, and mitochondrial membrane potential in both cell lines. The antioxidant system was disturbed as assessed by the increased activities in both catalase and superoxide dismutase. We demonstrated also, that TFM is an inductor of DNA damages quantified by the comet assay. Moreover, we showed an overexpression of proapoptotic Bax and a decrease in antiapoptotic Bcl‐2 expression. As a conclusion, we demonstrate that the liver presents the major target organ to TFM, in which the cytotoxicity and the genotoxic effects were significantly higher in hepatic cells than in renal cells and by consequence its uses must be controlled.